Effect of copper addition on microstructure and texture of TC4 titanium alloy manufactured by laser melting deposition - XIE Shao; LIU Yan; LI Junjie; ZHANG Zhenlin; CHEN Hui (Cailiao gongcheng)
Due to the large temperature gradient in the laser melting deposition process， the coarse primary β columnar grains with preferred orientation are formed along the deposition direction， resulting in significant anisotropy of materials. This study aims to change the morphology of the primary β grains， refine the microstructure and weaken the texture of titanium alloy by adding Cu element in the materials during the process of laser melting deposition. The effects of Cu content on the microstructure and texture of TC4 titanium alloy manufactured by laser melting deposition are studied systematically. The results show that Cu element addition can refine the columnar primary β grains significantly and make the grain size distribution more uniform. The columnar grains are transformed to fully equiaxed grains when 4% Cu （mass fraction， the same as below） is added into the material， and the average size of primary β grains decreases to 385 μm from 1490 μm of TC4 titanium alloy. Basket-weave microstructure composed of α-Ti， β-Ti， and a small amount of Ti2Cu is obtained inside primary β grains of the samples with Cu addition. The short rod-like Ti2Cu distributes at the boundary of the α-Ti lath， and its proportion in the microstructure increases with the increase of Cu addition. The average width of α-Ti is 0.44 μm when 8% Cu is added， which is reduced by about 63% compared with 1.18 μm of the sample without Cu addition. When 4% Cu is added， the maximum multiples of uniform distribution（MUD） value of α-Ti pole figure is reduced by about 71% compared with TC4 titanium alloy，which demonstrates that the addition of Cu can significantly reduce the texture strength of titanium alloy manufactured by laser melting deposition.